Reconfigurable radiation pattern of planar antenna using metamaterial for 5G applications - Ali Esmail, Bashar; A Majid, Huda; Zainal Abidin, Zuhairiah; Dahlan, Samsul Haimi; Himdi, Mohamed; Dewan, Raimi; A Rahim, Mohamad Kamal; AL-Fadhali, Najib (MDPI, 2020)
In this research, a reconfigurable metamaterial (MM) structure was designed using a millimeter-wave (MMW) band with two configurations that exhibit di erent refractive indices. These two MM configurations are used to guide the antenna’s main beam in the desired direction in the 5th generation (5G) band of 28 GHz. The di erent refractive indices of the two MM configurations created phase change for the electromagnetic (EM) wave of the antenna, which deflected the main beam. A contiguous squares resonator (CSR) is proposed as an MM structure to operate at MMW band. The CSR is reconfigured using three switches to achieve two MM configurations with di erent refractive indices. The simulation results of the proposed antenna loaded by MM unit cells demonstrate that the radiation beam is deflected by angles of +30 and